Implementasi Metode SAW dalam Sistem Pendukung Keputusan Pemilihan Smartphone Menggunakan Scratch - Riska Abdilana; Indra Igun Gunawan (Jurusan Informatika STTR Cepu, 2022)
The more smartphone developed, the more type of smartphone is released. The more that released, then the more varied the design, specifications and brand of phone that appears. So that makes prospective buyers having a hard time choosing a smartphone that suits their need. Therefore, researcher decided to build an application for smartphone selection which will make user easier to choose. The method used in the decision making system is Weighted Product method. Where this method is chosen because it can do calculation with multiplication to connect the attribute rating and produce the highest value that chosen as the best alternative. Then the user analysist is given to find out what else is needed for the 12 application users, so some question are given. Then a process design is carried out to determine whether the application made is in accordance with what is expected and also an activity to evaluate weakness of what being tested. The result is this application can be well received by respondent and also usefull in choosing a smartphone. The user can understand in using this application easily and this application give a positive value to every user that using it. In conclusion, users are made easier in choosing and knowing what smartphone is suitable for them. Suggestion, picture addition is needed so user can be more aware of what smarthpone they want.